Enhanced Physical Absorption Properties of ZnO Nanorods by Electrostatic Self-Assembly with Reduced Graphene Oxide and Decorated with Silver and Copper Nanoparticles - Yahiya, lina zeki; Dhahir, Mohamed K. (Iraqi Journal of Physics, 2021)
The preparation and characterization of innovative nanocomposites based on zinc oxide nanorods (ZNR) encapsulated by graphene (Gr) nanosheets and decorated with silver (Ag), and cupper (Cu) nanoparticles (NP) were studied. The prepared nanocomposites (ZNR@Gr/Cu-Ag) were examined by different techniques including Field Emission Scanning Electron Microscope (FESEM), Transmission electron microscopy (TEM), Atomic force microscopy (AFM), UV-Vis spectrophotometer and fluorescence spectroscopy. The results showed that the ZNR has been good cover by five layers of graphene and decorated with Ag and Cu NPs with particles size of about 10-15 nm. The ZNR@Gr/Cu-Ag nanocomposites exhibit high absorption behavior in ultraviolet (UV) region of spectrum. In comparison with ZNR, the ZNR@Gr/Cu-Ag nanocomposites reveal superior absorption in the entire region of 387–1000 nm. Moreover, the band gap decreases from 3.2 eV of ZNR to 1.2 eV for ZNR@Gr/Cu-Ag nanocomposites. Taking into account the superiority of ZNR@Gr/Cu-Ag nanocomposites in terms of easy fabrication, low cost method, and environmental friendliness which made it favorable for huge-scale preparation in many applications such as water splitting, sensor, solar cell, antibacterial and optoelectronic devices.